Pelatihan Penanganan Anak Demam Pada Kader Posyandu di Kelurahan Ledug Kecamatan Kembaran Kabupaten Banyumas - Etika Dewi Cahyaningrum; Murniati Murniati (LPPM Universitas Harapan Bangsa Purwokerto, 2022)
Fever in children often causes anxiety, stress, and phobias for parents. Inappropriate fever handling can be due to a lack of knowledge. Improving mothers' knowledge can be done by providing health education by posyandu cadres. The problem is that posyandu cadres do not know about fever and its handling, so training is needed. The method used is an approach, measuring the knowledge level of cadres about fever using a questionnaire, providing knowledge about fever (lectures, discussions), providing training in fever handling (roleplay, discussion), and re-measuring the knowledge level using questionnaires and follow-up/review fever handling. The training was attended by 46 posyandu cadres in Ledug Village, Kembaran District, and Banyumas Regency. The knowledge level of cadres at the first meeting obtained as many as 35 cadres with sufficient knowledge (76.09%); 7 cadres with good knowledge (15.22%), and 4 cadres with poor knowledge (8.69%), while at the second meeting, as many as 30 cadres had good knowledge (65.22%) and 16 cadres had sufficient knowledge (34.78 %). The success of this service can see from the increase in the cadre's knowledge about fever and its handling, namely being knowledgeable enough to be knowledgeable.